Polydisperse spray diffusion flames in oscillating flow. Issue 2 (3rd March 2016) - Greenberg, Jerrold Barry; Katoshevski, David
Abstract : The phenomenon of droplet clustering or grouping found when a spray of droplets is moving in an oscillating host flow field is investigated for the case of a polydisperse spray that fuels a laminar co-flow diffusion flame. A mathematical solution is developed for the liquid phase based on use of small Stokes numbers for size sections into which the polydisperse spray size distribution is divided. Droplet clustering in the oscillatory flow field is accounted for by constructing a special model for the sectional vaporization Damkohler numbers in accordance with droplet size. Combining this with a formal solution for a gas phase Schvab-Zel'dovich variable yields the means whereby flame dynamics can be described. Results calculated from this solution demonstrate that preferential droplet size behaviour (with smaller droplets tending to cluster to a greater extent and reduce the vaporization Damkohler number more than larger ones) can have a major impact on the flame dynamics through local droplet enrichment with attendant consequences on the production of fuel vapour. The dynamics of the sort of flame (over- or under-ventilated) and the occurrence of flame pinching leading to multiple flame sheets are altered under these circumstances. However, potential control of the actual initial spray polydispersity may reduce the intensity of such effects.